2023
DOI: 10.3390/cancers15020452
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Aptamers Targeting Ovarian Cancer Biomarker Human Epididymis Protein 4 for the Application in Urine

Abstract: Ovarian cancer is the deadliest gynecological cancer. With non-specific symptoms of the disease and the lack of effective diagnostic methods, late diagnosis remains the crucial hurdle of the poor prognosis. Therefore, development of novel diagnostic approaches are needed. The purpose of this study is to develop DNA-based aptamers as potential diagnostic probes to detect ovarian cancer biomarker Human epididymis protein 4 (HE4) in urine. HE4 is a protein overexpressed in ovarian cancer, but not in healthy or be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The results revealed that AHE1 and AHE3 exhibited a favorable affinity towards the target HE4, as evidenced by a dissociation constant measured within the nanomolar range. These compelling findings strongly indicate the potential of AHE1 and AHE3 as promising diagnostic probes, which could be further harnessed in the development of advanced diagnostic tests and biosensors intended for the reliable detection of OC [84].…”
Section: Human Epididymis Protein 4 (He4)mentioning
confidence: 92%
See 2 more Smart Citations
“…The results revealed that AHE1 and AHE3 exhibited a favorable affinity towards the target HE4, as evidenced by a dissociation constant measured within the nanomolar range. These compelling findings strongly indicate the potential of AHE1 and AHE3 as promising diagnostic probes, which could be further harnessed in the development of advanced diagnostic tests and biosensors intended for the reliable detection of OC [84].…”
Section: Human Epididymis Protein 4 (He4)mentioning
confidence: 92%
“…HE4 serum levels do not increase during pregnancy, menstruation, or in benign gynecological conditions. Additionally, HE4 is elevated at an earlier stage in the progression of the disease [84,89]. Nevertheless, the concentration of HE4 is substantially influenced by age [86].…”
Section: Human Epididymis Protein 4 (He4)mentioning
confidence: 99%
See 1 more Smart Citation
“…AHE3 and AHE1 are anti-HE4 aptamers, which bind to HE4 proteins in urine. Hence, these aptamers may be useful diagnostic tools for developing biosensors or urine tests for OC [ 74 ].…”
Section: Aptamersmentioning
confidence: 99%